Answer:
(x, y) = (-1, 9)
Explanations:
Given the system of equations expressed as:
4x + 8y = 68 .......................... 1
-12x + 3y = 39 ......................... 2
Using elimination method
Multiply equation 1 by 3 and equation 2 by 1 to eliminate the "x" variable as shown:
4x + 8y =68 ........................ 1 * 3
-12x + 3y = 39 .................... 2 * 1
___________________________________
12x + 24y = 204
-12x +3y = 39
Add the resulting equations to have;
24y + 3y = 204 + 39
27y = 243
y = 243/27
y = 9
Substitute y = 9 into equation 1 to solve for "x". From equation 1;
4x + 8y = 68
4x + 8(9) = 68
4x + 72 = 68
4x = 68 - 72
4x = -4
x = -4/4
x = -1
Therefore the solution to the system of equation is (-1, 9)